ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY, TOURISM PRODUCTS, AND LOCATION ON TOURIST INTEREST IN SVARGA SIMELIR, LANGKAT REGENCY - Mesra B; Annisa Febrina; Angga Pratama Sembiring (Yayasan Multidimensi Kreatif, 2025)
This research is motivated by an analysis of the influence of service quality, tourism products, and location on the interest of tourists visiting Svarga Simelir, Lalat Regency. The purpose of this study is to find out and analyze the influence of the quality of services, tourism products and tourist locations on the interest in visiting both partially and simultaneously. The approach used in this study is an associative approach. The population in this study is all tourists in the same district as Langkat Regency in 2024 as many as 22,486 people. The sample in this study used the slovin formula so that a sample of 100 svarga simelir tourists was obtained. The data collection technique in this study uses interview techniques, documentation studies, observations, and questionnaires. The data analysis techniques in this study used the Multiple Liner Regression Analysis Test, Hypothesis Test (t-test and F test), and Determination Coefficient. The data processing in this study uses the SPSS (Statistic Package for the Social Sciences) software program version 24.00. The results of this study prove that partially and simultaneously the quality of services, tourism products, and locations have a significant effect on the interest of tourists visiting Svarga Simelir, Lalat Regency.